PERFORMANSI PEMANAS AIR TENAGA SURYA DENGAN PENAMBAHAN SIRIP PADA PIPA KOLEKTOR - Himsar Ambarita; Firman Siahaan; Herdy -; H.V Sihombing (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2020)
The solar energy that reaches the earth's surface can be converted into heat energy using solar collectors. Inside the collector, there are several components including a heating pipe as a medium to drain water to the storage tank. There are several factors that increase the performance of solar collectors including the addition of fins to the pipe which will increase the collector's cross-sectional area. This study compares solar collectors with and without the addition of fins, the aim of improving the performance of solar water heater collectors with the addition of fins. Where the dimensions of the fins used are 50 x 12 x 0.3 mm. testing is done by comparing the two collectors. The results showed an increase in temperature in solar water heaters with the addition of fins to the pipe and an increase in efficiency of 18.67% compared to solar water heaters without the addition of fins.